Comparison of the Intraocular Pressure-Lowering Effect and Safety of Preservative-Free And Preservative-Containing Brimonidine/Timolol Fixed-Combination Ophthalmic Solutions in Patients with Open-Angle Glaucoma. (3rd April 2021) - Kim, Joon Mo; Kim, Tae-Woo; Park, Sang-Woo; Park, Hae-Young Lopilly; Hwang, Young Hoon; Jeoung, Jin Wook; Kim, Chan Yun
ABSTRACT: Purpose : To compare the therapeutic efficacy and safety of newly developed preservative-free (PF) brimonidine/timolol fixed-combination (BTFC) ophthalmic solutions and a preservative-containing (PC) BTFC ophthalmic solution in patients with open-angle glaucoma. Methods : This study was conducted as a multicenter, randomized, open-label, parallel-group clinical trial to evaluate the efficacy and safety of PF BTFC as compared with PC BTFC in adult patients (aged ≥ 19 years) with open-angle glaucoma (OAG) and ocular hypertension (OHT). A total of the 106 patients were enrolled, with 53 patients each randomized to the two treatment groups and included in the analysis of the safety set (SS). After a washout period, patients with an IOP below 35 mmHg at 9 a.m. were enrolled. After a full ophthalmic and glaucoma examination, a total of 106 OAG and OHT patients were randomized to the PF group or PC group. All subjects were examined 4 and 12 weeks after first administration. At each follow-up visit, IOP was measured at 9 a.m. and 11 a.m. and the efficacy, safety, and compliance were evaluated. Throughout the study, all adverse events were recorded and monitored by the investigators. Results The mean IOP changes from baseline to 12 weeks at 11:00 a.m. were −3.45 ± 2.53 mmHg in the PF group and −3.65 ± 2.76 mmHg in the PC group ( p < .0001 for both). The difference in mean IOP change between the two groups was 0.20 ± 2.65 mmHg, which was not significantly different. The proportion of patients with IOP reductions of ≥ 15% and ≥ 20% and IOP at all-time points in the PF group were not significantly different when compared with in the PC group. There were no specific differences between the two groups regarding the incidence of adverse events. Conclusions PF BTFC ophthalmic solution shows a similar efficacy and safety profile to that of PC BTFC.